Diagnosis Some Non-diatoms Phytoplankton Algae Near Three Pollution Sites Producing Dyes in Tigris River - Jiheel, Siham; Buthaina Al-Magdamy (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2026)
The presence and distribution of phytoplankton algae, which are related to water properties, are affected by these factors. Non-diatomic algae samples were collected during the autumn season in 2024-2025 from three sites on the Tigris River, including the Samarra pharmaceutical industry, woolen spinning factory, and paper waste landfill, to identify algae resistant to dye pollution. The study found slight temperature variations in three sites, with the highest temperature in the first site being 23.62 ºC and the lowest in the second site being 20.67 ºC. The water was found to be alkaline, with slightly reduced pH values at the first site. The electrical conductivity (EC) values were high, with the highest rate in the first site at 956.33 μs/cm and the lowest at 537.67 μs/cm. The total dissolved solids in water varied significantly at the three sites. The study found a rise in sulfate concentration at the first site (318.00 mg/l), while the lowest was at the third site (184.00 mg/l). High nitrate and phosphate concentrations were found at the first site (30.30 and 7.06 mg), while the lowest were at the third site (2.10 mg). The study identified 24 genera of phytoplankton algae, with Chlorophyte having the largest number (15 genera and 32 species), followed by Cyanophytae (14 species due to 8 genera) and Euglenophytae (one genus and species). The study also found differences in planktonic algae species in different sites, with blue-green algae having the highest percentage in the second and third sites, making them a target for studying biological purification of dyes.